Prevalence and incidence of sarcopenia in Swiss postmenopausal women: findings from the OsteoLaus Cohort - Colin Vendrami; Elena Gonzalez Rodriguez; Guillaume Gatineau; Peter Vollenweider; Pedro Marques-Vidal; Olivier Lamy; Didier Hans; Enisa Shevroja (Swiss Medical Weekly)
STUDY AIMS: Sarcopenia is a progressive, age-related loss of muscle mass, strength and function. Given the ageing population and the adverse outcomes associated with sarcopenia, monitoring its epidemiology is particularly important. This study aimed to describe sarcopenia prevalence, 5-year incidence and agreement between definitions using the latest operational criteria in Swiss postmenopausal women.